2018
DOI: 10.1016/j.ihj.2018.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Erectile dysfunction severity as a predictor of left main and/or three-vessel disease in acute coronary syndrome patients

Abstract: BackgroundCoronary artery disease (CAD) is a leading cause of morbidity and death. Early diagnosis of patients with left main and/or three-vessel disease (LM/3VD) among acute coronary syndrome (ACS) patients is beneficial. The relation between erectile dysfunction (ED) and cardiovascular diseases was previously noticed. The aim of our work was to find out if the severity of ED could predict the presence of LM/3VD in ACS patients.Patients and methodsEighty-five male patients with ACS were included in the study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…They concluded that the angiographic severity of CAD was found to be more in patients with moderate or severe ED. 14 In conrast, in a study on male patients with type II diabetes and CAD, Gazzaruso et al. reported that ED was significantly more prevalent in type II diabetic males with CAD, however, they did not find a significant relationship between ED severity and CAD severity, and between IIEF-5 score and Gensini score.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…They concluded that the angiographic severity of CAD was found to be more in patients with moderate or severe ED. 14 In conrast, in a study on male patients with type II diabetes and CAD, Gazzaruso et al. reported that ED was significantly more prevalent in type II diabetic males with CAD, however, they did not find a significant relationship between ED severity and CAD severity, and between IIEF-5 score and Gensini score.…”
Section: Discussionmentioning
confidence: 92%
“… 16 Previous studies have used the Gensini score as a sub-parameter, but for the first time, our study evaluated the relationship between Gensini score and ED severity. 13 , 14 , 15 In the study involving 85 patients with ACS, Al-Daydamony et al comparing patients with IIEF score ≥ 17 (mild or no ED) and patients with IIEF score < 17 (moderate or severe ED), they found patients with moderate or severe ED had significantly higher mean Gensini score. They concluded that the angiographic severity of CAD was found to be more in patients with moderate or severe ED.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This predictor is additionally linked to the presence of severe coronary artery disease (Sanchez‐Nadales et al., 2023 ). Elderly patients exhibited a higher prevalence of severe and extensive coronary disease (Al‐Daydamony et al., 2018 ; D'Ascenzo et al., 2012 ; Salimi et al., 2023 ). This variable examined in our study was also identified as a predictor of LM/3VD with an SS greater than 22.…”
Section: Discussionmentioning
confidence: 99%
“…e risk of acute coronary syndrome (ACS) is evident in many of subjects with ED [33]. Extensive involvement of coronary arteries in terms of left main and three-vessel disease was reported in ACS patients who suffered from moderate or severe ED [34]. ED predicts poor outcome such as rehospitalization and death in patients with acute MI [35].…”
Section: Discussionmentioning
confidence: 99%